Effect of coriander extract and soaking time in culture of three barley cultivars and identification of the active compounds by a device GCMS - Ibrahim, Mohammed A.; Hayawi, Jassim A.; Sultan, Fatima I. (Journal of Kerbala for Agricultural Sciences, 2022)
The research was carried out in one of the laboratories of the Plant Production Techniques Department at the Agricultural Technical College / Mosul, in plastic trays with dimensions (9 x 15) cm, perforated from the bottom to drain excess water. The research included three factors, the first factor was the aqueous extract of coriander plant at two levels (comparator treatment and coriander extract), the second factor was the duration of soaking at two levels (6 and 12) hours, the third factor was barley varieties with three levels (local black barley, white Rayhan barley, Zanbaqa barley), and the use of a complete randomized design (CRD) according to the factorial experiment system and with three replications, at the end of the research, the data were recorded, and they were statistically analyzed using the computer according to the SAS program, and the different averages were distinguished by different alphabets, and the results were as follows: coriander extract outperformed the comparison treatment in terms of total wet weight, dry weight, and length of gesture. However, soaking for (12) hours was significantly superior to soaking for (6) hours in total wet and dry weight and seedling length, and that the cultivar Rayhan was significantly superior to the local black and Zanbaqa cultivars in the total wet and dry weight, thickness and number of roots. The interaction between coriander extract and soaking time (12) hours significantly exceeded the total wet and dry weight and seedling length. The interaction between coriander extract and Rayhan cultivar, as well as the interaction between soaking time (12) hours and Rayhan cultivar, and triple interaction between coriander extract and soaking duration (12) hours and Rayhan cultivar, achieved significant superiority in all studied traits. GCMS and it was found that there are 8 phenolic compounds and two fatty acids. We conclude through this study that aqueous coriander extract showed the behavior of growth regulators.